Density of Hydroxyapatite-Gelatin Composite Scaffolds Derived from Blue Swimming Crab Shells - Nadhiva Qothrunnada; Widi Widayat (Journal of Creativity Student, 2026)
Hydroxyapatite-gelatin composite scaffolds have potential applications in bone tissue engineering as they combine the bioactive properties of hydroxyapatite with the capability of gelatin as a polymer matrix. This study aims to analyze the density of hydroxyapatite-gelatin composite scaffolds derived from blue swimming crab shells at varying gelatin concentrations of 2%, 3%, and 4%. Hydroxyapatite was synthesized from blue swimming crab shell powder through a microwave-assisted precipitation method, followed by characterization using X-ray diffraction (XRD). The scaffolds were fabricated via the slurry casting method using a total mass of 4 g of the hydroxyapatite-gelatin mixture. Density testing was conducted on three specimens for each variant using the hydrostatic weighing method based on Archimedes' principle, with 96% ethanol as the immersion fluid. The XRD characterization results demonstrated that the synthesized powder was dominated by a hydroxyapatite phase at 99.6%, with minor phases of calcite at 0.3% and portlandite at 0.1%. The average densities of the scaffolds at gelatin concentrations of 2%, 3%, and 4% were 2.161 g/cm³, 2.259 g/cm³, and 2.321 g/cm³, respectively. Descriptively, an increase in gelatin concentration within the tested range was followed by an increase in the average scaffold density. Further testing on porosity, morphology, mechanical properties, degradation, and biocompatibility is required to determine the more optimal scaffold composition.